Strategy To Achieve Birth Certificate Ownership In Kalisidi Village, West Ungaran Sub-District - Tri Wida Yanti; Arief Sadjiarto; Destri Sambara Sitorus (Jurnal Administrasi Publik (Public Administration Journal), 2021)
This study aims to determine the strategy of the village government in optimizing the achievement of ownership of birth cerificates with a focus on the management function and strategy management. This study used descriptive qualitative method. The research instrument was the researcher itself using primary and secondary data sources. Data collection techniques used were observation, interviews and documentation. The strategy of the Kalisidi village government was based more on management functions (planning, organizing, directing and controlling) and supported by strategic management. Planning started with regional mapping, team planning, team preparation planning, socialization planning and evaluation planning. Organizing was done by forming a team of hamlet and RT heads as the person in charge of the hamlet and the administrative staff as the village coordinator. Directing and controlling the team did not experience difficulties because each team had done the activity well. The obstacle of analyzing the external environment were the distance and the people's livelihood. Through this combination can produce solutions and solutions for the implementation of further activities.